The Effect of Financial Experience and Economic Rationality on The Economic Decision of Household Women in Jambi City Mediated By Economic - Ahmad Rifki; Cipto Wardoyo; Lisa Rokhmani (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to determine the effect of financial experience and economic rationality on the economic decisions of Jambi city housewives mediated by economic literacy. This study uses a quantitative method with a type of explanatory research. The research sample is 379 housewives in the districts of Pelayangan and Danau Teluk. Data analysis uses Structural Equation Modeling (SEM) with smartPLS 3.0 software. The results of the study show 1) Financial Experience Has a Positive and Significant Influence on the Economic Decisions of Housewives, 2) Economic Rationality Has No Influence and is Not Significant on the Economic Decisions of Housewives, 3) Economic Literacy Has a Positive and Significant Influence on the Economic Decisions of Housewives, 4) Financial Experience Has a Positive and Significant Influence on the Economic Literacy of Housewives, 5) Economic Rationality Has a Positive and Significant Influence on the Economic Literacy of Housewives, 6) Financial Experience Has a Positive and Significant Influence on the Economic Decisions of Housewives Through Economic Literacy as a Mediating Variable, 7) Rationality Economics Has a Positive and Significant Influence on the Economic Decisions of Housewives Through Economic Literacy as a Mediating Variable. The implications of the research: 1) Economic literacy strengthens the effect of financial experience and economic rationality on economic decisions, 2) Housewives need to improve their financial experience, good economic rationality, and economic literacy so they can make the right economic decisions. This increase is necessary because the economic situation is sometimes less stable and difficult to predict.